Empirically derived consequences to treat rumination. (20th December 2019) - Migan‐Gandonou, Julyse A.; Leon, Yanerys
Abstract : We evaluated a contingent oral hygiene procedure on rumination emitted by a 9‐year‐old boy with autism. Results of a functional analysis screening suggested rumination was maintained by automatic reinforcement. We conducted a stimulus avoidance assessment to identify a hierarchy of potential consequences to be used in treatment. During treatment, contingent toothbrushing resulted in a 97% decrease in rumination. Finally, we transitioned to a less intrusive intervention (i.e., contingent mouthwash spray) and rumination remained at near‐zero levels. Treatment effects generalized to different settings and caregivers and maintained over a 4‐year period.